BOLALAR MUSIQIY QOBILIYATLARINI RIVOJLANTIRISHINING O’ZIGA XOS XUSUSIYATLARI - Boboxonova, F. (SCIENCE and SOCIETY, 2019)
The article is devoted to the study of content and methods of working with the pupils of primary classes at the secondary educational schools with badly-developed musical abilities. The author of the article also characterizes psychological and physiological state of the pupils.
Keywords: musical ability; comparative ability; musical hearing; unison; chair